HITUNG TROMBOSIT DI SINDROM KORONER AKUT TERKAIT LOW MOLECULAR WEIGHT HEPARIN (LMWH) - Cyntia Kornelius; Darwati Muhadi; Mansyur Arif (Indonesian Association of Clinical Pathologist and Medical laboratory, 2012)
Heparin and Low molecular weight heparin (LMWH) had been used widely for prevention and treatment of thrombosis in the patients with acute coronary syndrome (ACS). Actually, the administration of heparin may caused some adverse effect, such as heparin inducedthrombocytopenia (HIT). This study was aimed to reveal thrombocytes count in patients with ACS who underwent LMWH therapy. An observational study with cohort prospective design was performed in 30 patients with ACS. The thrombocytes count was obtained from complete blood count (CBC) by using haematology analyzer (Sysmex XT 2000i) that performed at Clinical Pathology Laboratory, Dr. Wahidin Sudirohusodo Hospital, Makassar. The obtained data was analyzed with Wilcoxon test. The mean thrombocytes count before the administration of LMWH was 236.800/μL, while mean thrombocytes count after the administration of LMWH was 280.270/μL. Suprisingly this data showed that in general thrombocytes count was increased significantly (P=0.004) five day after starting LMWH therapy. In this study only one (3.3%) of 30 patients who received LMWH had trombocytes count less than 150.000/μL. Based on this study an antibody test to PF4-heparin complex was needed to determined occurance of HIT in this patient. The thrombocytes count was increased significantly (P=0.004) in patients with ACS who had given LMWH therapy.